GrAHal-CAPP for axion dark matter search with unprecedented sensitivity in the 1–3 μeV mass range - Pugnat, Pierre; Camus, Philippe; Kwon, Ohjoon; Ballou, Rafik; Bruyère, Cyril; Byun, Heesu; Chung, Woohyun; Grenet, Thierry; Perrier, Pierre; Semertzidis, Yannis K.; Talarmin, Arthur; Vessaire, Jérémy (Frontiers in Physics, 2024)
A collaboration between CNRS-Grenoble and IBS-CAPP Daejeon plans to build a Sikivie’s type haloscope for axion/ALPs dark matter search at the Dine-Fischler-Srednicki-Zhitnitskii sensitivity for the 300–600 MHz range. It will be based on the large-bore superconducting “outsert” coil of the Grenoble hybrid magnet, providing a central magnetic field up to 9 T in an 810-mm warm bore diameter. This magnet has recently been successfully powered up to 8.5 T, achieving the first step of the electrical commissioning phase. The design principles of the cryostat with its double dilution refrigerators to cool below 50 mK, the light Cu RF cavity of 700-mm diameter, and its tuning rod(s) and the first stages of the measurement chain are presented. Perspectives for the targeted sensitivity assuming less than a 2-year integration time are given.